Should systematic prostatic biopsies be discontinued? - Klotz, Laurence (Prostate cancer and prostatic diseases, 2025)
Introduction The use of systematic biopsies in addition to targeted biopsies is based on multiple studies showing that 15–20% of “clinically significant” cancers are missed on targeted biopsies. Concern about these ‘missed’ cancers drives many interventions. This includes systematic biopsies in men with negative imaging and in men having targeted biopsies, and drives a preference for total gland treatment in men who may be candidates for partial gland ablation. This article summarizes recent genomic and clinical data indicating that, despite “clinically significant” histology, MRI invisible lesions are genomically and clinically favorable. These studies have demonstrated that the genetic aberrations associated with cancer visibility are the same aberrations that drive cancer invasiveness and metastasis. Thus invisible cancers, even if undiagnosed at baseline, are in most cases indolent and pose little threat to the patient. The implications are that patients should be monitored with imaging rather than systematic biopsy, and subject to repeat targeted biopsy for evidence of MR progression. Patients prefer this strategy. It has many advantages in terms of reduced burden of care, cost, psychological benefits, and less diagnosis of insignificant cancer. Conclusion It is now appropriate to abandon systematic biopsies in most patients.